Volume 2C: Turbomachinery 2014
DOI: 10.1115/gt2014-26475
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Performance of a Transonic Turbine Blade Passage in Presence of Upstream Slot and Mateface Gap With Endwall Contouring

Abstract: The present study investigates mixed out aerodynamic loss coefficient measurements for a high turning, contoured endwall passage under transonic operating conditions in presence of upstream purge slot and mateface gap. The upstream purge slot represents the gap between stator-rotor interface and the mateface gap simulates the assembly feature between adjacent airfoils in an actual high pressure turbine stage. While the performance of the mateface and upstream slot has been studied for lower Mach number, no stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Although this ejected fluid can locally increase heat transfer significantly (>200% relative to the upstream endwall), it is also a source of cooling air. A series of studies with realistic endwall conditions and endwall contouring in a transonic facility by Jain et al [20] and Roy et al [21] also concluded that a majority of the gap leakage flow was located near the throat, and that a contoured endwall improved coolant distribution relative to a flat endwall.…”
Section: Relevant Past Studiesmentioning
confidence: 99%
“…Although this ejected fluid can locally increase heat transfer significantly (>200% relative to the upstream endwall), it is also a source of cooling air. A series of studies with realistic endwall conditions and endwall contouring in a transonic facility by Jain et al [20] and Roy et al [21] also concluded that a majority of the gap leakage flow was located near the throat, and that a contoured endwall improved coolant distribution relative to a flat endwall.…”
Section: Relevant Past Studiesmentioning
confidence: 99%
“…The losses were attributed to mixing within the gap, and were shown to be relatively independent of platform gap net flowrate. Measurements in a transonic cascade by Jain et al [10] led them to conclude that the presence of the platform gap (without net flow) resulted in a 5% increase in overall loss, but introduction of net gap flow had negligible effect. In contrast, Piggush and Simon [3] found a small increase in the loss for increased gap flow, but loss did not change for net flowrates above 1% of the mainstream flow.…”
Section: Relevant Past Studiesmentioning
confidence: 99%
“…However, most of these studies focus on the endwall heat transfer and cooling performance. With regard to the aerodynamic performance, Jain et al 19 investigated the aerodynamic performance of a transonic turbine blade passage in the presence of upstream slot and midgap with nonaxisymmetric endwall contouring. In their work, numerous conditions test were conducted but the case of the nonaxisymmetric endwall without midgap was not provided thus the disadvantage of the design without considering the midgap was not clear.…”
Section: Introductionmentioning
confidence: 99%